2016
DOI: 10.1093/hmg/ddw063
|View full text |Cite
|
Sign up to set email alerts
|

Defective membrane fusion and repair inAnoctamin5-deficient muscular dystrophy

Abstract: Limb-girdle muscular dystrophies are a genetically diverse group of diseases characterized by chronic muscle wasting and weakness. Recessive mutations in ANO5 (TMEM16E) have been directly linked to several clinical phenotypes including limb-girdle muscular dystrophy type 2L and Miyoshi myopathy type 3, although the pathogenic mechanism has remained elusive. ANO5 is a member of the Anoctamin/TMEM16 superfamily that encodes both ion channels and regulators of membrane phospholipid scrambling. The phenotypic over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

14
117
1
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(133 citation statements)
references
References 60 publications
14
117
1
1
Order By: Relevance
“…ANO5 is likely to be a phospholipid scramblase because it is 65% identical to ANO6 in the transmembrane domains and it contains a scramblase domain nearly identical to the one we described in ANO6 (22, 40). Knockout of ANO5 in mice phenocopies human limb girdle muscular dystrophy type 2L (LGMD2L) (102). Ano5 -deficient mice exhibit delayed regeneration of muscle after cardiotoxin injury.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…ANO5 is likely to be a phospholipid scramblase because it is 65% identical to ANO6 in the transmembrane domains and it contains a scramblase domain nearly identical to the one we described in ANO6 (22, 40). Knockout of ANO5 in mice phenocopies human limb girdle muscular dystrophy type 2L (LGMD2L) (102). Ano5 -deficient mice exhibit delayed regeneration of muscle after cardiotoxin injury.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the number of nuclei per myotube was greatly reduced in Ano5 −/− cells. (102). Because humans with ANO5 myopathies and Ano5 knockout mice have no obvious muscle phenotypes at birth, this suggests that ANO5 may not play a significant role in myoblast fusion during embryogenesis but may be more important in satellite cell fusion in the adult.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…ANO5 is primarily localized to skeletal muscle and thyroid and is localized intracellularly within the endoplasmic reticulum . The function of ANO5 is not well known, but high sequence similarity to ANO6 suggests that it may behave as a scramblase . A recent study by Griffin et al in which they investigated normal ANO5 function, revealed that the protein may be involved in repair of muscle membranes following injury, similar to dysferlin .…”
mentioning
confidence: 99%